Analysis of the possibilities of increasing the energy efficiency of absorption refrigeration appliances through the use of refrigerating accumulators - Berezovska, Liudmyla; Titlov, Oleksandr (Technology audit and production reserves, 2023)
One of the most important tasks of modern society is the solution of environmental and energy problems in power engineering and, in particular, refrigeration technology. At the same time, in the field of artificial cooling systems, it is necessary to solve the problems of reducing the impact on both the ozone layer and the greenhouse effect. An effective approach here can be absorption refrigeration systems with a natural working fluid (water-ammonia solution), which does not adversely affect the environment. For the effective use of absorption refrigeration systems, it is necessary to solve the problems of increasing their energy efficiency, in particular, through the use of cold accumulators. Thus, the object of research is absorption-type cooling systems with cold accumulators. The paper analyzes cold accumulators with different physical nature. It is shown that melting substances can be the most effective for solving problems of low-temperature cooling. An analysis of the thermal scheme of an absorption freezer of the «chest» type, which is the most problematic in terms of providing cooling modes at a level of (–18)–(–24) °С, was carried out. Optimization thermal calculations for typical absorption freezers up to 200 dm3 have been performed. It is shown that when the chamber is initially loaded with a product at an ambient temperature, the cooling capacity of the installed absorption refrigeration units is not enough – no more than 50 % of the required one. For an absorption freezer of the «chest» type, the most suitable cold-storage materials are a eutectic aqueous solution of sodium chloride or propylene glycol, since these solutions have the desired melting point of the order of –18 °C and a fairly high melting heat. The result of optimizing the weight and size characteristics of the internal volume of the absorption freezer is the following recommendations: – the optimal size of wire baskets for placing products is 315´370´240 mm; – the gaps between the basket and the cabinet wall, as well as between the baskets themselves, should be 10 mm to ensure normal convection conditions; – it is not advisable to place fans inside the volume of the freezer at this stage, since the freezing time is reduced by a maximum of 30 %, but this results in additional heat generation, energy consumption and increases the shrinkage of the products stored in the chamber.